The spontaneous control of HIV replication is characterized by decreased pathological changes in the gut-associated lymphoid tissue (2018)
ABSTRAC: Background: HIV infection induces alterations in the gut-associated lymphoid tissue (GALT) that constitutes the most important site for viral replication due to the extensive presence of effector memory T-cells. In the case of HIV-controllers, several studies have reported fewer periph eral alterations and conserved immune responses that correlate with viral control; however, the histopathological characterization of GALT in those patients is still missing. In this study, we evalu ated pathological alterations in GALT, trying to associate them with clinical parameters of HIV in fected patients with or without evidence of viral control.